2008
DOI: 10.1007/s11060-008-9590-9
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of the STAT3 signaling pathway with a decoy oligonucleotide suppresses growth of human malignant glioma cells

Abstract: Gliomas are the most common type of primary tumor in the human central nervous system. STAT3, a signal transducer and activator of transcription 3, is over expressed in gliomas. Its involvement in tumorgenesis can be attributed to its ability to induce cell proliferation and inhibit apoptosis. Double-stranded decoy oligodeoxynucleotides (ODNs) which correspond closely to the STAT3 response element within the c-fos promoter are a potential tool for inhibiting a variety of tumor cell growth. To investigate its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 26 publications
1
38
2
Order By: Relevance
“…Our results obtained in C6 glioma cells with Stat3 decoy are in apparent disagreement with the results obtained by Gu et al [2008] in two glioma cell lines: U251 and A172. Upon transfecting those cells with the same Stat3 decoy, the authors observed downregulation of Bcl2l1, Myc, and Ccnd1, as well as decreased cell viability.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results obtained in C6 glioma cells with Stat3 decoy are in apparent disagreement with the results obtained by Gu et al [2008] in two glioma cell lines: U251 and A172. Upon transfecting those cells with the same Stat3 decoy, the authors observed downregulation of Bcl2l1, Myc, and Ccnd1, as well as decreased cell viability.…”
Section: Discussioncontrasting
confidence: 99%
“…Primers used to detect Stat3 expression were 5′-GGGTCTGGCTAGACAATAT (Gu et al 2008); survivin, 5′-TTGGCAGGTGCCTGTTGAAT -3′ and 5′-AGC CAGTCCCCCACAGCAT -3′ (Shinozawa et al 2000); MMP-2, 5′-GTGCTGAAGGACACACTAAAGAAGA -3′ and 5′-TTGCCATCCTTCTCAAAGTTGTAGG -3′ ; and primers against β-actin as a positive control were 5′-CCAAGGCCAACCGCGAGAAGATGAC -3′ and 5′-AGGGTACATGGTGGTGCCGCCAGAC -3′. After amplification, polymerase chain reaction products were electrophoresed on a 1% agarose gel and visualized by ethidium bromide staining.…”
Section: Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
“…Previous studies have demonstrated that blockade of Stat3 signaling induces cell apoptosis (Konnikova et al 2003;Gao et al 2005;Nam et al 2005;Gu et al 2008;Ren et al 2008). Annexin V Assay was used to examine the apoptosis cells after transfecting Stat3 shRNA.…”
Section: Stat3 Rnai Induces Glioma Cell Line U251 Apoptosismentioning
confidence: 99%
“…Galiellalactone (Weidler et al, 2000;Hellsten et al, 2008), flavopiridol (Lee et al, 2006) and a class of platinum (IV) compounds including IS3295 (Turkson et al, 2005), CPA-1, CPA-7 and platinum (V) tetrachloride (Turkson et al, 2004b), and decoy oligodeoxynucleotides (Xi et al, 2005;Zhang et al, 2007;Gu et al, 2008;Sun et al, 2008;Zhang et al, 2010;Barton et al, 2004) were found to interfere with Stat3 binding to DNA as well as induce cell growth inhibition and apoptosis of human breast, lung and prostate cancer cells (Hellsten et al, 2008;Barton et al, 2004;Zhang et al, 2010;Zhang et al, 2007;Xi et al, 2005;Sun et al, 2008;Gu et al, 2008;Turkson et al, 2004b;Turkson et al, 2005;Lee et al, 2006). Some of these inhibitors have been tested in animal models and they appear to cause regression of xenograft tumors.…”
Section: Stat3 Transcription Factormentioning
confidence: 99%